THE EFFECT OF PERFORMANCE RECOGNITION AND WORK-LIFE BALANCE ON EMPLOYEE PERFORMANCE WITH EMPLOYEE JOB SATISFACTION AS AN INTERVENING VARIABLE AT PT. BANK MANDIRI OUTLET PRIORITY OF MEDAN PULAU PINANG - Angela Kezia Sianturi; Prihatin Lumbanraja2; Nismah Penjaitan (CV. Radja Publika, 2025)
This study aims to analyze the effect of performance recognition and work-life balance on employee job satisfaction at PT. Bank Mandiri Priority Outlet Medan Pulau Pinang. It also examines the influence of performance recognition, work-life balance, and employee job satisfaction on employee performance at the same institution. Additionally, it investigates the indirect effect of performance recognition and work-life balance on employee performance through employee job satisfaction. The research employs an associative method, with a sample of 93 employees. Path analysis was conducted using SPSS 27 software. The results indicate that performance recognition has a positive and significant effect on employee job satisfaction. Work-life balance also positively and significantly influences employee job satisfaction. Performance recognition, work-life balance, and job satisfaction each have a positive and significant direct effect on employee performance. Furthermore, performance recognition and work-life balance indirectly and positively influence employee performance through the mediating role of job satisfaction